Pemanfaatan Abu Ampas Tebu Sebagai Bahan Substitusi Semen Terhadap Karakteristik Bata Beton Pejal - Afwan Eka Putra; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of bagasse ash in the manufacture of solid concrete bricks is one way of saving in the use of cement. Concrete brick is a type of brick-shaped building material made from the main ingredients of portland cement, water, and aggregates used for wall pairs. The study of the use of bagasse ash aims to determine the effect of bagasse ash on the quality of concrete bricks, namely in terms of compressive strength and water absorption. Comparison of the mass of cement with sand is 1: 4. The method used is to conduct experiments in the laboratory. The results showed that the relationship between compressive strength and concrete brick water absorption was inversely proportional. The greater the compressive strength of the concrete brick, the smaller the absorption value of the water and vice versa. In terms of compressive strength, the maximum value of using bagasse ash to obtain concrete brick of quality level I is the percentage of 22.5% with a compressive strength of 103.077 kg / cm2. The conclusion that can be taken in this study is the use of bagasse ash can reduce cement usage by 30% in the manufacture of concrete bricks. This is evidenced by the results of the quality of concrete bricks obtained still meet the requirements of SNI 03-0349-1989 with a quality level II. Keywords: Solid concrete brick, bagasse ash, compressive strength, water absorption